Implementation of the Independent Campus Learning Policy in Higher Education - Herianto, Edy; Setyowati, Raden Roro Nanik; Nurlaela, Nurlaela (Universitas Negeri Surabaya, 2024)
The research aims to describe the implementation of the MBKM policy. This is a phenomenological type of qualitative research, namely examining the problem as a phenomenon in depth and finding patterns of connection between phenomena. Data was collected with the help of interviews, observation, and documentation techniques. All data obtained were analyzed qualitatively. The results of the research show that (1) FKIP Universitas Mataram, FISH Universitas Negeri Surabaya, and FT Universitas Negeri Makassar have implemented the MBKM policy, (2) the implementation of MBKM has had an impact on increasing students' self-confidence in obtaining additional competencies beyond core competencies according to the program study, (3) supporting factors in the form of the availability of BKP options for students, the challenge factor of limited supporting funds and BKP implementation tools, and (4) as an essential part of determining key performance indicators (IKU)of higher education institution, it is necessary to adjust the implementation of MBKM policy constantly.